pengaruh pendidikan kesehatan tentang inspeksi visual asam asetat test terhadap pengetahuan dalam pencegahan kanker serviks di desa Godekan Mojolaban Surakarta - Ardhila, Nura, Arina Maliya, S.Kep., M.Si.Med, Fahrun Nur Rosyid, S.Kep., Ns., M.Kes (2016)
Cervical cancer was an important health problem for women around the world. Cervical cancer was a malignancy that occurs in the cervix and was caused by infection with the Human Papilloma Virus (HPV). One of the prevention of cervical cancer was with early detection of cervical cancer. Problems in the community showed a lot of people who are less aware of the importance of early examination of cervical cancer, so it was necessary efforts to increase public knowledge about the early detection of cervical cancer. This study aims to determine the effect of health education on prevention pengetahuandalam IVA Test against cervical cancer in women in the village Godegan Mojolaban Sukoharjo. This study was a Quasi-experimental research and research methods with quantitative research design in the form of a draft Non Equaivalen Control group design. Samples were 40 women ranging in age from 30-60 years old in the village Godegan were divided into two groups by simple random sampling technique. Collecting data using questionnaires were analyzed using the Wilcoxon Signed Rank Test and Mann Whitney Test. Conclusion of the study are (1) knowledge in the prevention of cervical cancer in women in the village Godegan Mojolaban Sukoharjo before giving health education (pre-test) in both groups were mostly less, (2) further knowledge on the post test in the treatment group was mostly good whereas in the group mostly less control, and (3) there are significant health education of IVA Test of knowledge in the prevention of cervical cancer in the village Godegan Mojolaban Sukoharjo. keyword : health education, knowledge of IVA Test, the prevention of cervical cancer